Relações entre ensino de ciências e matemática e minorias sociais na Amazônia : contribuições dos egressos da terceira turma da REAMEC - Santos, Jusiany Pereira da Cunha dos (2022)
The research that originated this thesis was produced with the objective of understand the relations between the trajectory of the graduates of the third class (2015-2019) of the Graduate Program in Education and Science and Mathematics of the Amazon Network of Science and Mathematics Education (PPGECEM/REAMEC) and the social minorities, based on perceptions about the doctoral training process and the impacts of their research in the Amazon region. Because of this, was adopted a qualitative approach of the Case Study type, with one deeply analysis on a specific topic within a broader context (a case about the study). Therefore, the first stage had the participation of 55 graduates and, through the analysis of their curriculum available on the Lattes Platform (CL), the profile of the graduates of the third class was built. In the second stage, an online questionnaire was applied, which was made available to all graduates of the third group through emails and was answered by 28 graduates, with the purpose of complementing information from the CL and analyzing the occupational situation and formation in the PPGECEM, listing the Program's strengths and weaknesses. In the last stage, to establish relationships between social minorities and the science and mathematics’ education, the analysis of the thesis of PPGECEM/REAMEC graduates was carried out, which address the theme "social minorities" (2011, 2013, 2015 and 2017’ classes), with an in broad study of the eight thesis of the 2015’ class (third class), in the context of the Brazilian Legal Amazon (ALB). As a result, was found the relevance of program in this highlighted region, since 22 theses were produced on this theme by the graduates of the first four PPGECEM/REAMEC’ classes, so that one concerns the Quilombola school, three to rural education, seven to indigenous education and 11 to Disabilities (one related to Inclusive Education, two to Deafness, one to TEA, one to Intellectual Disability and five to Visual Disability). In conclusion, the thesis defended in this study is based on the principle that: research’s by PPGECEM/REAMEC Graduates contributes with the quality of science and mathematics’ teaching in the Amazon region towards the reduction of social and regional inequalities in our country, although all the efforts made by institutions and researcher-teachers are still insufficient.